Cerium oxide nanoparticles reduce the accumulation of autofluorescent deposits in light-induced retinal degeneration: Insights for age-related macular degeneration. (October 2020) - Tisi, A.; Passacantando, M.; Lozzi, L.; Maccarone, R.
Abstract: Accumulation of lipofuscin deposits in the retinal pigment epithelium (RPE) is one of the main events involved in age-related macular degeneration and its increase together with RPE dysfunction, blood retinal barrier disruption and photoreceptors death progressively leads to blindness. Lipofuscin is the main autofluorescent (AF) component of the retina and therapies to counteract its deposition are a main goal to be achieved, since effective treatments have not yet been identified. Here, we first investigated the spatio-temporal pattern of AF deposits accumulation in the light-damage model of age-related macular degeneration. Afterward, we tested the ability of cerium oxide nanoparticles, a well known anti-oxidant agent, to counteract AF granules accumulation. The treatment was performed both before and after the induction of the degeneration. AF granules were quantified by confocal microscopy on whole mounted retinas. We demonstrated that the acute light-damage increases the accumulation of AF deposits in the hot spot retina in terms of number of granules and percentage of occupied area, with a peak 7 days after the exposure. Remarkably, cerium oxide nanoparticles showed a strong efficacy in preventing the formation of AF deposits when they were injected 3 days before light exposure. Moreover, when the treatment was performed 7 days after light exposure, nanoceria activity was found to be effective also in reducing the amount of the AF granules still deposited up to 60 days. These important results represent the very first evidence about the ability of cerium oxide nanoparticles to counteract AF deposits accumulation in retinal degeneration, laying the foundations for the development of a new therapy possibly targeting lipofuscin in AMD. Highlights: Acute light damage induces massive autofluorescence deposits accumulation in the rat retina. Preventive treatment with nanoceria inhibits autofluorescence deposits accumulation. Nanoceria promote removal of retinal autofluorescence deposits.